Positive electrode material and preparation method thereof
A core-shell structured positive electrode material with higher core porosity improves lithium ion transport and structural stability, addressing issues of high nickel cathode materials in lithium ion batteries, enhancing performance and safety.
Patent Information
- Application Number
- JP2023563298
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-06-28
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-06-28
AI Technical Summary
Cathode materials with high nickel content face issues such as rapid capacity loss, poor safety, and structural instability due to phase transitions, uneven lithium distribution, and electrolyte oxidation, which affect the performance and safety of lithium ion batteries.
A positive electrode material is designed with a core and shell structure, where the core has higher porosity than the shell, facilitating lithium ion transport and structural stability, achieved through controlled coprecipitation processes.
The core-shell structure enhances lithium ion transport, reduces structural stress, and improves cycling properties and safety of lithium ion batteries, particularly those with high energy density.
Smart Images

Figure 0007602063000001 
Figure 0007602063000002 
Figure 0007602063000003
Abstract
Description
[Technical field]
[0001] The present invention relates to lithium ion batteries, and in particular to a positive electrode material in the form of secondary particles having a core and a shell, and a method for preparing the same. [Background technology]
[0002] With the rapid development of electric vehicles, the requirements for their mileage, service life, and safety are becoming increasingly stringent. Therefore, batteries, one of the key components in electric vehicles, are also facing great challenges. The performance and safety of batteries for electric vehicles are closely related to their cathode materials, and research is focused on cathode materials. LiNi x Co y Mn 1-x-y Ternary materials such as O2 are one of the widely used positive electrode materials. As the requirements for battery energy density increase, the content of nickel in the ternary materials is constantly increasing.
[0003] Cathode materials with high nickel content may face issues such as rapid capacity loss and poor safety. The main reasons may include: (1) During delithiation in high-nickel-content cathode materials, various phase transitions occur, which can lead to internal stresses and strains in the particles, resulting in particle breakage, an increase in crumbling sites in the material, and structural collapse. (2) The uneven distribution of lithium ions in the positive electrode material and the disorder of Li / Ni adversely affect the channels transporting lithium ions, and the cycle life and safety of the material are also adversely affected. (3) When charging a positive electrode material with a high nickel content, the surface Ni 4+ can oxidize the electrolyte and generate gas, which has a significant impact on the safety of the battery.
[0004] Various methods have been proposed in the prior art to improve the internal crystal structure and interfacial stability of high-nickel content cathode materials, thereby improving the rate capability, cycleability, and safety of the materials, which may include coating, doping with impurities, controlling particle size, etc.
[0005] Chinese Patent No. 108269970 relates to a gradient doped positive electrode active material, which has a good balance between large capacity and extended cycle characteristics in addition to good interfacial stability.Chinese Patent No. 110422889 relates to a gradient doped positive electrode active material, which has the advantages of large discharge capacity and good cycle characteristics. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Chinese Patent No. 108269970 [Patent Document 2] Chinese Patent No. 110422889 Summary of the Invention [Problem to be solved by the invention]
[0007] Improvements in electrical performance have been achieved in the prior art by modifying the composition of the positive electrode material, however, there remains a need to modify the positive electrode material in other ways to further improve its performance. [Means for solving the problem]
[0008] In order to meet the above requirements, the present invention provides a cathode material in the form of secondary particles having a core and a shell, the porosity of the core being greater than that of the shell, and a method for preparing the same. The structure at least ensures that the voids between the primary particles in the core are greater than the voids between the primary particles in the shell. The structure of the present invention can effectively improve the battery performance and safety of the cathode material, and is therefore particularly suitable for lithium-ion batteries with high energy density. Moreover, the method for preparing the cathode material is simple.
[0009] In one aspect, the present invention provides a method for producing a pharmaceutical composition comprising: 1. A positive electrode material for a lithium ion battery in the form of secondary particles having a core and a shell, A cathode material is provided in which the porosity of the core is greater than the porosity of the shell.
[0010] In another aspect, the present invention provides a method for preparing a cathode material for a lithium ion battery in the form of secondary particles having a core and a shell, the method comprising:
[0011] (1) subjecting a solution of soluble salts containing Ni, Co, and M and a dispersion containing D to a first coprecipitation to form cores of secondary particles; (2) subjecting a solution of soluble salts containing Ni, Co, and M and a dispersion containing G to a second coprecipitation in the presence of the cores of step (1) to form shells on the cores, thereby obtaining secondary particles having a core and a shell, the first co-precipitation is carried out at a pH lower than the pH of the second co-precipitation and at a temperature lower than the temperature of the second co-precipitation; a porosity of the core is greater than a porosity of the shell; (3) a step of converting the secondary particles obtained in step (2) into the positive electrode material, the step including contacting the secondary particles obtained in step (2) with a lithium source material at 300 to 900° C. to obtain the positive electrode material, the lithium source material is one or more of Li2O, LiOH, LiOH·H2O, LiNO3, and Li2CO3; Where: M is one or two of Mn and Al; D is one or more of Mo, Ti, Y, W, Ta, Nb, Cr, Sm, Sb, V, La, Ca, Hf, and Zr; G is one or more of Mo, Ta, Zn, Ti, Y, Zr, W, Nb, Cr, Sm, Al, V, La, Ca, Sb, Hf, Mg, and B. Effect of the Invention
[0012] Compared with the prior art, the present invention has the following advantageous effects:
[0013] (1) The porosity of a positive electrode material means that the material has a porous structure, which facilitates the transport of lithium ions and, as a result, improves battery performance such as rate characteristics. (2) The porosity of the core in the positive electrode material is larger than that of the shell, which means that the voids between the primary particles in the core are different from the voids between the primary particles in the shell, which reduces the possibility of cracks occurring due to stress and strain in the material, thereby achieving the purpose of stabilizing the material structure. (3) The porosity of the core in the positive electrode material is larger than that of the shell, which further indicates that the shell is relatively dense, which improves the structural stability of the material and, consequently, improves the cycling property and safety of the material. (4) According to a preferred embodiment of the present invention, some pores in the positive electrode material will increase in pore volume under pressure as the pressure increases. This can be attributed to the fact that the pressure opens closed pores in the positive electrode material and exposes new pores. This means that the positive electrode material according to the present invention can reduce the problem caused by the collapse of the positive electrode material due to the pressure generated during the operation of the battery, and as a result, improve the cycle characteristics of the battery. [Brief description of the drawings]
[0014] The accompanying drawings are included to provide a further understanding of the invention and are incorporated in and constitute a part of this specification, and together with the following detailed description are intended to explain the invention and are not intended to limit its scope. [Figure 1] 1 shows an SEM image of the positive electrode material of Example 1. [Diagram 2] 1 shows an SEM image of a local cross section of the positive electrode material of Example 1. [Diagram 3] 1 shows an SEM image of a local cross section of the positive electrode material of Example 1. [Figure 4] 1 shows cycle characteristics of coin cells fabricated using the positive electrode materials of Example 1, Comparative Example 1, and Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Except for the examples, all numerical values of parameters in this specification should be understood to be modified in all instances by "about," regardless of whether the term "about" actually precedes the numerical value.
[0016] In one embodiment, the present invention relates to a cathode material for a lithium-ion battery in the form of secondary particles having a core and a shell, wherein the porosity of the core is greater than the porosity of the shell.
[0017] The term "secondary particles" as used herein refers to particles formed by aggregation of multiple primary particles. In one embodiment, secondary particles according to the invention have a spherical shape or a nearly spherical shape, such as an ellipsoid. In one variant, secondary particles according to the invention have a particle size on the order of micrometers, such as 1 to 100 micrometers.
[0018] Typically, nickel-containing positive electrode materials are in the form of flakes and accumulate in primary particles that have an elongated shape and a maximum dimension of 300-500 nm.
[0019] The primary particles themselves may be porous. At the same time, the secondary particles made up of the primary particles may be porous. There are voids between the primary particles that make up the secondary particles. Thus, as a whole, the positive electrode material has a porous structure. The porous structure includes macropores (diameter 50-500 nm), mesopores (20-50 nm), and micropores (2-20 nm). The porosity of the positive electrode material according to the present invention is mainly due to the macropores. The macropores are mainly voids between the primary particles.
[0020] The porous structure of the cathode material according to the present invention can be defined by "porosity". In the present invention, porosity = (1-ρ1 / ρ2) × 100%, where ρ1 is the compacted density and ρ2 is the true density. Compacted density refers to the measurement of the density of the cathode material when it is compressed by an external force to fill the voids (macropores) between the primary particles in the cathode material. True density refers to the measurement of the density of the cathode material when it is completely compressed to remove all pores. Compacted density and true density can be measured directly using a compacted density meter and a true density meter, respectively.
[0021] In the process of testing compacted density according to the present invention, the cathode material is uniformly compressed up to 20 kN for 30 minutes.
[0022] In one variant, the porosity of the core is 50-90%, preferably 60-80%, and the porosity of the shell is 10-50%, preferably 20-40%. Preferably, the ratio of the porosity of the core to the porosity of the shell is greater than 1.2, preferably greater than 1.5, for example 1.5-5.0, preferably 2.0-2.5.
[0023] In a modification, the core includes macropores with a pore diameter of 50 to 500 nm, and the porosity of the macropores in the core is 60 to 80%, preferably 65 to 75%. The shell includes macropores with a pore diameter of 50 to 500 nm, and the porosity of the macropores in the shell is 20 to 40%, preferably 25 to 35%.
[0024] In a modification, the pore volume of the positive electrode material increases as the pressure applied to the positive electrode material increases. Preferably, the pore volume under pressure of pores with a pore diameter of 50 to 110 nm in the positive electrode material is PV i which may be recorded as, where i is 0, 1, 2, 3, and 4, corresponding to the pore volumes of the pores when pressures of 0 ton, 1.5 tons, 2.5 tons, 3.5 tons, and 4.5 tons are applied to the positive electrode material, respectively. The pore volume under pressure satisfies the formulas 1 < PV1 / PV0 < 1.5, 1 < PV2 / PV0 < 4.0, 1 < PV3 / PV0 < 6.0, and 1 < PV4 / PV0 < 8, preferably the formulas 1 < PV1 / PV0 < 1.4, 1 < PV2 / PV0 < 3.5, 1 < PV3 / PV0 < 5.5, and 1 < PV4 / PV0 < 7.5.
[0025] There is no specific limitation on the composition of the positive electrode material of the present invention. It may be a doped nickel-containing positive electrode material generally used in this technology. In a modification, the average composition of the positive electrode material is Li 0.6+δ [(Ni x1 Co y1 M 1-x1-y1 D η1 ) z ·(Ni x2 Co y2 M 1-x2-y2 G η2 ) 1-zO2, where 0 ≦ δ ≦ 0.6, 0.6 ≦ x1 ≦ 1, 0.6 ≦ x2 ≦ 1, 0 ≦ y1 ≦ 0.4, 0 ≦ y2 ≦ 0.4, 0 < z < 1, 0 ≦ η1 ≦ 0.1, 0 ≦ η2 ≦ 0.1. Here, M is one or two of Mn and Al, D is one or more of Mo, Ti, Y, W, Ta, Nb, Cr, Sm, Sb, V, La, Ca, Hf, and Zr, and G is one or more of Mo, Ta, Zn, Ti, Y, Zr, W, Nb, Cr, Sm, Al, V, La, Ca, Sb, Hf, Mg, and B. Preferably, in the cathode material, 0.7 ≦ x1 < 1, 0.7 ≦ x2 < 1, 0 < y1 ≦ 0.3, 0 < y2 ≦ 0.3, 0 < η1 ≦ 0.05, 0 < η2 ≦ 0.05, 0.4 ≦ z ≦ 0.5, 1 - x1 - y1 - η1 is not 0, and 1 - x2 - y2 - η2 is not 0.
[0026] In a modification, D and G each have a concentration gradient in the core and shell of the cathode material. Preferably, in the cathode material, the concentration of D gradually decreases radially from the center of the core to the surface of the core, and the concentration of G gradually increases radially from the surface of the core to the surface of the shell. In the cathode material, nickel, cobalt, and M (i.e., manganese and / or aluminum) may each have a concentration gradient. For example, the concentration of manganese gradually increases radially from the center of the core to the surface of the core, and the concentration of nickel gradually decreases radially from the surface of the core to the surface of the shell.
[0027] In a further embodiment, the present invention provides a method for preparing a cathode material for a lithium-ion battery in the form of secondary particles having a core and a shell. The method includes (1) subjecting a solution of a soluble salt containing Ni, Co, and M and a dispersion containing D to a first coprecipitation to form a core of secondary particles; (2) subjecting a solution of a soluble salt containing Ni, Co, and M and a dispersion containing G to a second coprecipitation in the presence of the core of step (1) to form a shell on the core, thereby obtaining secondary particles having a core and a shell, the first co-precipitation is carried out at a pH lower than the pH of the second co-precipitation and at a temperature lower than the temperature of the second co-precipitation; a porosity of the core is greater than a porosity of the shell; (3) converting the secondary particles obtained in step (2) into the positive electrode material by contacting the secondary particles obtained in step (2) with a lithium source material at 300 to 1000° C. to obtain the positive electrode material, the lithium source material is one or more of Li2O, LiOH, LiOH·H2O, LiNO3, and Li2CO3; Where: M is one or two of Mn and Al; D is one or more of Mo, Ti, Y, W, Ta, Nb, Cr, Sm, Sb, V, La, Ca, Hf, and Zr; G is one or more of Mo, Ta, Zn, Ti, Y, Zr, W, Nb, Cr, Sm, Al, V, La, Ca, Sb, Hf, Mg, and B.
[0028] In one variation, step (1) involves carrying out the first coprecipitation at a pH of 9 to 12.5, preferably 10 to 12, and step (2) involves carrying out the second coprecipitation at a pH of 10 to 13, preferably 11 to 13. Preferably, the pH in the first coprecipitation is lower than the pH in the second coprecipitation by 0.5 to 2, preferably 0.5 to 1. Preferably, step (1) involves carrying out the first coprecipitation at 45 to 65°C, preferably 50 to 60°C, and step (2) involves carrying out the second coprecipitation at 50 to 70°C, preferably 55 to 65°C.
[0029] In a variant, step (1) comprises carrying out a first coprecipitation in the presence of a complexing agent, and step (2) comprises carrying out a second coprecipitation in the presence of a complexing agent. Preferably, the complexing agent used in the first coprecipitation has a concentration of 5-12 mol / L, preferably 7-10 mol / L, and the complexing agent used in the second coprecipitation has a concentration of 0.1-5 mol / L, preferably 0.5-4.5 mol / L. Preferably, the complexing agent used in the first coprecipitation has a higher concentration than the complexing agent used in the second coprecipitation, for example by 3.0-9.0 mol / L. The complexing agent used in the first coprecipitation is the same as the complexing agent used in the second coprecipitation or is different from the complexing agent used in the second coprecipitation. The complexing agent is one or more selected from the group consisting of ammonia, ammonium sulfate, ammonium chloride, and ammonium nitrate.
[0030] In some variations, the soluble salt of nickel is one or more selected from the group consisting of nickel sulfate, nickel chloride, nickel nitrate, and nickel acetate. The soluble salt of cobalt is one or more selected from the group consisting of cobalt sulfate, cobalt chloride, cobalt nitrate, and cobalt acetate. When M is manganese, the soluble salt of manganese is one or more selected from the group consisting of manganese sulfate, manganese chloride, manganese nitrate, and manganese acetate. When M is aluminum, the soluble salt of aluminum is one or more selected from the group consisting of sodium aluminate and alumina sol.
[0031] In one variation, the dispersion of D may be a sol containing elemental D or a solution containing a soluble salt of D, such as one or more solutions selected from the group consisting of sulfate, hydrochloride, and nitrate salts of D.
[0032] In one variation, the dispersion of G may be a sol containing elemental G or a solution containing a soluble salt of G, such as one or more solutions selected from the group consisting of sulfate, hydrochloride, and nitrate salts of G.
[0033] In a variant, the concentration or flow rate of the dispersion of D is controlled in step (1) such that the concentration of D gradually decreases radially from the center of the core to the surface of the core. The concentration or flow rate of the dispersion of G is controlled in step (2) such that the concentration of G gradually increases radially from the surface of the core to the surface of the shell. Preferably, the dispersion of D is added in step (1) with a gradually decreasing concentration, and the dispersion of G is added in step (2) with a gradually increasing concentration. Preferably, the dispersion of D is added in step (1) with a gradually decreasing flow rate, and the dispersion of G is added in step (2) with a gradually increasing flow rate.
[0034] In a variant, one or two of a precipitant, an antioxidant, and a processing aid are added to the first and second co-precipitations. The precipitant is one or more selected from the group consisting of sodium hydroxide, potassium hydroxide, and lithium hydroxide. The antioxidant is one or more selected from the group consisting of ascorbic acid, sodium bisulfite, and tea polyphenols. The processing aid is one or more selected from the group consisting of polyvinylpyrrolidone, polyvinyl alcohol, and sodium dodecyl sulfate. The amounts of precipitant, antioxidant, and processing aid added are well known to those skilled in the art.
[0035] In a variant, the first and second coprecipitations may be carried out under a protective atmosphere, which may be one or more selected from the group consisting of nitrogen and an inert gas. The inert gas may be, for example, argon.
[0036] In a variant, step (3) of converting the secondary particles obtained in step (2) into a positive electrode material may comprise calcining the secondary particles obtained in step (2) together with a lithium source material at 300-1000° C., preferably 500-900° C., for 1-36 h, preferably 6-24 h. Preferably, the lithium source material is one or more of Li2O, LiOH, LiOH·H2O, LiNO3, and Li2CO3, preferably LiOH or LiOH·H2O. Preferably, the calcination is carried out under an oxygen-containing atmosphere, for example in the presence of air or oxygen.
[0037] The positive electrode material according to the present invention may be used in a secondary battery, such as a lithium ion battery. The lithium ion battery may include a negative electrode, a positive electrode, a separator, and an electrolyte.
[0038] The positive electrode includes a positive electrode material layer on a positive current collector, the positive electrode material layer including the positive electrode material according to the present invention. The positive electrode material layer may further include a binder and a conductive agent. The binder may be a resin material selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylonitrile (PAN), styrene butadiene rubber (SBR), carboxymethyl cellulose (CMC), and the like. The conductive agent may include a carbon-based material or a conductive polymer. The carbon-based material may include, for example, graphite, acetylene black, carbon fiber, nanotubes, graphene, and carbon black. The conductive polymer may include polyaniline, polythiophene, polyacetylene, polypyrrole, and the like. The current collector may include at least one of stainless steel, aluminum, nickel, iron, titanium, copper, tin, or any other conductive material known to one skilled in the art. In some variations, the current collector may be pre-coated, such as aluminum foil pre-coated with carbon.
[0039] There is no particular limitation on the composition of the negative electrode of the present invention, and it may be any negative electrode commonly used in the art, such as a lithium metal sheet.
[0040] There is no particular limitation on the composition of the separator of the present invention. It may be a separator commonly used in the art. For example, the separator may be a porous membrane made of polyolefin such as polytetrafluoroethylene, polypropylene, or polyethylene.
[0041] The electrolyte may be any of a variety of conventional electrolytes, such as a non-aqueous electrolyte. The non-aqueous electrolyte is a solution formed by a non-aqueous solvent containing an electrolyte lithium salt. Any conventional non-aqueous electrolyte known to those skilled in the art may be used. For example, the electrolyte may be at least one selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), and lithium hexafluorosilicate (LiSiF6). The non-aqueous solvent may be selected from the group consisting of linear esters, cyclic esters, and mixtures thereof. The linear ester may be at least one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), and dipropyl carbonate (DPC). The cyclic ester may be at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), and vinylene carbonate (VC). EXAMPLES
[0042] The features and advantages of the present invention will become apparent from the following examples, which are intended to illustrate, but not to limit, the present invention.
[0043] Test Method 1. Scanning electron microscope examination The morphology of the samples was characterized using a scanning electron microscope, specifically a Hitachi High Tech Group Smartlab tester, at magnifications of 3000x and 10000x.
[0044] 2. Compaction density test The compacted density of the samples was characterized using a compacted density meter, specifically, a Mitsubishi Chemical (Japan) MCP-PD51 tester. The samples were uniformly compressed up to 20 kN for 30 min, and the test results were obtained from the test software.
[0045] 3. True density test The true density of the samples was characterized using a true density meter, specifically an AccuPyc 1340 tester manufactured by Micromeritics (USA). The test results were obtained from the test software.
[0046] 4. Pore size and pore volume testing The adsorption curves of the samples were obtained using a Tri-star 3020 specific surface area analyzer manufactured by Micromeritics (USA). The samples were pretreated under the conditions of a heating temperature of 300°C and a degassing time of 120 minutes. The pore size of the samples was calculated by the BJH method, and the pore volume of the samples was calculated by the BET method.
[0047] 5. Testing the change in pore volume under pressure Pressures of 0, 1.5, 2.5, 3.5, and 4.5 tons were applied to 3 g of sample to obtain compressed samples. The above tests of pore size and pore volume were repeated for each compressed sample to obtain data on the pore volume of pores with a pore size of 90±10 nm, i.e., PV0, PV1, PV2, PV3, and PV4. The ratios of PV1, PV2, PV3, and PV4 to PV0 were calculated, respectively, to characterize the change in pore volume of pores with a pore size of 90±10 nm under pressure.
[0048] 6. Battery performance testing 6.1 Preparation of battery samples A positive electrode slurry was prepared by mixing 9.2 g of the positive electrode active material sample, 0.4 g of acetylene black, and 0.4 g of polyvinylidene fluoride (PVDF). The positive electrode slurry was applied to an aluminum foil, dried, and pressed at 100 MPa to form a shape with a diameter of 12 mm and a thickness of 120 μm. The shape was then dried at 120° C. for 12 hours in a vacuum drying oven to obtain a positive electrode plate.
[0049] A Li metal sheet with a diameter of 17 mm and a thickness of 1 mm was used as the negative electrode. A porous polyethylene film with a thickness of 25 μm was used as the separator. A 1.0 mol / L LiPF6 solution was used as the electrolyte, and a mixture of equal amounts of ethylene carbonate (EC) and diethyl carbonate (DEC) was used as the solvent.
[0050] The positive plate, separator, negative plate, and electrolyte were used to assemble a 2025 coin cell.
[0051] 6.2 Performance evaluation of cell samples (1) Initial specific discharge capacity The prepared coin cell samples were left for 24 hours. The samples were charged to a cut-off voltage of 4.3 V at a current density of 20 mA / g, and then charged at a constant voltage of 4.3 V for 30 minutes. They were then discharged to a cut-off voltage of 3.0 V at a current density of 20 mA / g. The discharge time was recorded. The initial specific discharge capacity of the cell sample = current density × discharge time.
[0052] (2) Cycle characteristics The cell sample was charged and discharged twice at a current density of 20 mA / g and a cutoff voltage of 3.0-4.3 V to complete the activation of the cell sample. The activated cell sample was subjected to a certain number of charge-discharge cycles (e.g., 80 cycles) at a current density of 1 C, a voltage range of 3.0-4.3 V, and 45° C. As described above, the specific discharge capacity of each cycle was obtained from the current density and discharge time of each cycle. The cycle performance of the cell sample was characterized by the capacity retention at high temperature, where the capacity retention at high temperature = specific discharge capacity of a particular cycle / initial specific discharge capacity × 100%.
[0053] Comparative Example 1 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.88:0.05:0.07 to produce a 1.5 mol / L aqueous solution of transition metal salts. Nano-ZrO2 was mixed with water to produce a 0.5 mol / L solution of Zr dopant. The aqueous solution of transition metal salts, the solution of Zr dopant, 6.0 mol / L NaOH, and 3.0 mol / L NH3·H2O were slowly added to the reactor under stirring. Coprecipitation was carried out at 55°C with pH 12.0 under N2 atmosphere. After 70 hours of reaction, secondary particles with a total particle size of 14.2 μm were obtained.
[0054] The secondary particles were mixed with lithium hydroxide, corresponding to a ratio of Li / (Ni+Co+Mn)=1.04, and calcined at 735°C for 15 hours in an oxygen atmosphere to obtain a comparative positive electrode material CC-1. 1.04 Ni 0.88 Co 0.05 Mn 0.06 Zr 0.01 It was O2.
[0055] The performance of the comparative cathode material CC-1 was tested as described above. The test results showed that the comparative cathode material CC-1 did not have a core-shell structure and had a porosity of 65%. The change in pore volume under pressure for the comparative cathode material CC-1 was PV1 / PV0=0.1, PV2 / PV0=0.3, PV3 / PV0=0.6, and PV4 / PV0=0.7 for the pore volume corresponding to a pore diameter of 90±10 nm.
[0056] The cycle characteristics of a coin cell prepared using the comparative positive electrode material CC-1 of Comparative Example 1 are shown in FIG.
[0057] Comparative Example 2 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.88:0.05:0.07 to produce a 1.5 mol / L aqueous solution of transition metal salts. Nano-ZrO2 was mixed with water to produce a 0.5 mol / L solution of Zr dopant. The aqueous solution of transition metal salts, the solution of Zr dopant, 6.0 mol / L NaOH, and 3.0 mol / L NH3·H2O were slowly added to the reactor under stirring. The first coprecipitation was carried out at 60°C with pH 12.5 under N2 atmosphere. After 40 h of the first coprecipitation, the second coprecipitation was carried out at 55°C with 8.0 mol / L NH3·H2O under N2 atmosphere at pH 11.0. After 30 h of the second coprecipitation, secondary particles with a total particle size of 14.1 μm were obtained.
[0058] The secondary particles were mixed with lithium hydroxide, corresponding to a ratio of Li / (Ni+Co+Mn)=1.04, and calcined at 735°C for 15 hours in an oxygen atmosphere to obtain a comparative positive electrode material CC-2. 1.04 Ni 0.88 Co 0.05 Mn 0.06 Zr 0.01 It was O2.
[0059] The performance of the comparative cathode material CC-2 was tested as described above. The test results showed that the comparative cathode material CC-2 had a core-shell structure, with the core having a radius of 1.5 μm, as shown by the results of scanning electron microscopy. The results of the pore size, porosity, and pore volume tests showed that the shell porosity was 71% and the core porosity was 30%. The change in pore volume under pressure for the comparative cathode material CC-1 was PV1 / PV0=0.05, PV2 / PV0=0.1, PV3 / PV0=0.6, and PV4 / PV0=1.233 for the pore volume corresponding to a pore size of 90±10 nm.
[0060] The cycle characteristics of a coin cell prepared using the comparative positive electrode material CC-2 of Comparative Example 2 are shown in FIG.
[0061] Comparative Example 3 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.97:0.02:0.01 to produce a 1.5 mol / L aqueous solution of transition metal salts (1). Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.94:0.02:0.04 to produce a 1.5 mol / L aqueous solution of transition metal salts (2). Nano Nb2O5 was mixed with water to produce a 0.5 mol / L solution of Nb dopant (3) and a 0.01 mol / L solution of Nb dopant (4). The aqueous solution of transition metal salts (2) was added to the aqueous solution of transition metal salts (1) at a flow rate of 0.2 L / h to produce a mixed aqueous solution of transition metal salts. The Nb dopant solution (4) was added to the Nb dopant solution (3) at a flow rate of 0.1 L / h to generate a mixed Nb dopant solution. At the same time, the mixed aqueous solution of transition metal salts, the mixed Nb dopant solution, 6.0 mol / L NaOH, and 3.0 mol / L NH3·H2O were slowly added to the reactor under stirring. The first coprecipitation was carried out at 55°C under N2 atmosphere at pH 12.0. The first coprecipitation was carried out for 40 hours.
[0062] Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.86:0.05:0.09 to produce a 1.5 mol / L aqueous solution of transition metal salts (5). Nano-ZrO2 was mixed with water to produce a 0.01 mol / L solution of Zr dopant (6) and a 1.0 mol / L solution of Zr dopant (7). The Zr dopant solution (7) was added to the Zr dopant solution (6) at a flow rate of 0.1 L / h to produce a mixed solution of Zr dopant. At the same time, under stirring, the aqueous solution of transition metal salts (2), the mixed solution of Zr dopant, 6.0 mol / L NaOH, and 3.0 mol / L NH3·H2O were slowly added to the reactor where the first coprecipitation had just finished. The second coprecipitation was carried out under N2 atmosphere at pH 12 and 55 °C. After 30 hours of the second coprecipitation, the addition of the aqueous solution of transition metal salt (5) was stopped, and after another 0.5 hour reaction, secondary particles with a total particle size of 14.0 μm were obtained.
[0063] The secondary particles were mixed with lithium hydroxide, corresponding to a ratio of Li / (Ni+Co+Mn)=1.04, and calcined at 735°C for 15 hours in an oxygen atmosphere to obtain a comparative positive electrode material CC-3. The composition was Li[(Ni 0.95 Co 0.02 Mn 0.02 Nb 0.01 ) 0.014 ·(Ni 0.875 Co 0.05 Mn 0.07 Zr 0.005 ) 0.986 ]O2. In the core of the comparative positive electrode material CC-3, the Nb content decreased from a molar content of 0.02 mol% to 0 as it moved radially from the center of the core to the surface of the core. Meanwhile, the Mn content increased from a molar content of 0.01 mol% to 0.03 mol% as it moved radially from the center of the core to the surface of the core. The total amount of Nb and Mn remained at 0.03 mol%. In the shell of the comparative positive electrode material CC-3, the Zr content increased from a molar content of 0 to 0.01 mol% as it moved radially from the surface of the core to the surface of the shell. Meanwhile, the Ni content decreased from a molar content of 0.91 mol% to 0.85 mol% as it moved radially from the surface of the core to the surface of the shell. Moreover, the Mn content increased from a molar content of 0.04 mol% to 0.08 mol% as it moved radially from the surface of the core to the surface of the shell.
[0064] The performance of the comparative cathode material CC-3 was tested as described above. The test results showed that the comparative cathode material CC-3 had a core-shell structure, with the core having a radius of 1.7 μm, as shown by the results of scanning electron microscopy. The results of the pore size, porosity, and pore volume tests showed that the shell porosity was 33% and the core porosity was 33%. The change in pore volume under pressure for the comparative cathode material CC-3 was PV1 / PV0=0.1, PV2 / PV0=0.3, PV3 / PV0=0.6, and PV4 / PV0=0.8 for the pore volume corresponding to a pore size of 90±10 nm.
[0065] The coin cell fabricated using the comparative positive electrode material CC-3 of Comparative Example 3 had a capacity retention rate of 91.5% after 80 cycles.
[0066] Comparative Example 4 Comparative Example 3 was repeated to obtain a comparative positive electrode material CC-4, which had the same chemical composition as the comparative positive electrode material CC-3, except that the first co-precipitation was carried out with 3.0 mol / L NH3·H2O under a N2 atmosphere at pH 12.5 at 60°C, and the second co-precipitation was carried out with 8.0 mol / L NH3·H2O under a N2 atmosphere at pH 11.5 at 55°C.
[0067] The performance of the comparative cathode material CC-4 was tested as described above. The test results showed that the comparative cathode material CC-4 had a core-shell structure, with the core having a radius of 3.4 μm, as shown by the results of scanning electron microscopy. The results of the pore size, porosity, and pore volume tests showed that the shell porosity was 73% and the core porosity was 32%. The change in pore volume under pressure for the comparative cathode material CC-4 was PV1 / PV0=0.05, PV2 / PV0=0.1, PV3 / PV0=0.6, and PV4 / PV0=1.2 for the pore volume corresponding to a pore size of 90±10 nm.
[0068] The coin cell fabricated using the comparative positive electrode material CC-4 of Comparative Example 4 had a capacity retention rate of 89.2% after 80 cycles.
[0069] Example 1 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.97:0.02:0.01 to produce a 1.5 mol / L aqueous solution of transition metal salts (1). Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.94:0.02:0.04 to produce a 1.5 mol / L aqueous solution of transition metal salts (2). Nano Nb2O5 was mixed with water to produce a 0.5 mol / L solution of Nb dopant (3) and a 0.1 mol / L solution of Nb dopant (4). The aqueous solution of transition metal salts (2) was added to the aqueous solution of transition metal salts (1) at a flow rate of 0.2 L / h to produce a mixed aqueous solution of transition metal salts. The Nb dopant solution (4) was added to the Nb dopant solution (3) at a flow rate of 0.1 L / h to generate a mixed Nb dopant solution. At the same time, the mixed aqueous solution of transition metal salts, the mixed Nb dopant solution, 6.0 mol / L NaOH, and 8.0 mol / L NH3·H2O were slowly added to the reactor under stirring. The first coprecipitation was carried out at 53°C under N2 atmosphere at pH 11.0. The first coprecipitation was carried out for 60 hours.
[0070] Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.86:0.05:0.09 to produce a 1.5 mol / L aqueous solution of transition metal salts (5). Nano-ZrO2 was mixed with water to produce a 0.01 mol / L solution of Zr dopant (6) and a 1.0 mol / L solution of Zr dopant (7). The Zr dopant solution (7) was added to the Zr dopant solution (6) at a flow rate of 0.1 L / h to produce a mixed solution of Zr dopant. At the same time, under stirring, the aqueous solution of transition metal salts (5), the mixed solution of Zr dopant, 6.0 mol / L NaOH, and 3.0 mol / L NH3·H2O were slowly added to the reactor where the first coprecipitation had just finished. The second coprecipitation was carried out under N2 atmosphere at pH 11.5 and 58 °C. After 40 hours of the second coprecipitation, the addition of the aqueous solution of transition metal salt (5) was stopped, and after another 0.5 hour reaction, secondary particles with a total particle size of 14.0 μm were obtained.
[0071] The secondary particles were mixed with lithium hydroxide, corresponding to a ratio of Li:(Ni+Co+Mn)=1.04, and calcined at 735°C for 15 hours under an oxygen atmosphere to obtain a cathode material C-1. The composition was Li[(Ni 0.95 Co 0.02 Mn 0.02 Nb 0.01 ) 0.014 ·(Ni 0.875 Co 0.05 Mn 0.07 Zr 0.005 ) 0.986 ]O2. In the core of the positive electrode material C-1, the Nb content decreased from a molar content of 0.02 mol% to 0 as it moved radially from the center of the core to the surface of the core. Meanwhile, the Mn content increased from a molar content of 0.01 mol% to 0.03 mol% as it moved radially from the center of the core to the surface of the core. The total amount of Nb and Mn remained at 0.03 mol%. In the shell of the positive electrode material C-1, the Zr content increased from a molar content of 0 to 0.01 mol% as it moved radially from the surface of the core to the surface of the shell. Meanwhile, the Ni content decreased from a molar content of 0.91 mol% to 0.85 mol% as it moved radially from the surface of the core to the surface of the shell. Moreover, the Mn content increased from a molar content of 0.04 mol% to 0.08 mol% as it moved radially from the surface of the core to the surface of the shell.
[0072] The performance of the cathode material C-1 was tested as described above.
[0073] The results of the scanning electron microscope test are shown in Figures 1 to 3. As shown in Figures 1 to 3, the positive electrode material C-1 was a spherical particle with a core-shell structure. The radius of the core was 1.7 μm, and the outer radius of the shell was 5.3 μm. The core and shell had different voids.
[0074] According to the results of the pore size, porosity, and pore volume tests, the porosity of the core was 70% and the porosity of the shell was 32%. The change in pore volume under pressure for the positive electrode material C-1 was PV1 / PV0=0.6, PV2 / PV0=2.7, PV3 / PV0=3.5, and PV4 / PV0=4.9 for the pore volume corresponding to a pore size of 90±10 nm.
[0075] The cycle characteristics of the coin cell prepared using the positive electrode material C-1 of Example 1 are shown in Figure 4. As shown in Figure 4, compared with the comparative positive electrode materials of Comparative Example 1 and Comparative Example 2, the positive electrode material C-1 of Example 1 had a higher capacity retention rate after the same number of cycles. The coin cell prepared using the positive electrode material C-1 of Example 1 had a capacity retention rate of 93.9% after 80 cycles.
[0076] Example 2 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.89:0.055:0.055 to produce a 1.5 mol / L aqueous solution of transition metal salts (1). Nano-ZrO2 was mixed with water to produce a 0.5 mol / L solution of Zr dopant (2). Nano-Nb2O5 was mixed with water to produce a 0.5 mol / L solution of Nb dopant (3). The aqueous solution of transition metal salts (1), the Zr dopant solution (2), the Nb dopant solution (3), 6.0 mol / L NaOH, and 8.0 mol / L NH3·H2O were slowly added to the reactor under stirring. The first coprecipitation was carried out under N2 atmosphere at pH 11.5 at 54 °C. After the first coprecipitation for 60 h, the second coprecipitation was carried out with 2.5 mol / L NH3·H2O under N2 atmosphere at pH 12.5 and 58 C. After the second coprecipitation for 40 h, secondary particles with a total particle size of 14.1 μm were obtained.
[0077] The secondary particles were mixed with lithium hydroxide in a ratio of Li:(Ni+Co+Mn)=1.04 and calcined at 735°C for 15 hours in an oxygen atmosphere to obtain the cathode material C-1. 1.05 [(Ni 0.95 Co 0.05 Mn 0.015 Nb 0.015 ) 0.10·(Ni 0.905 Co 0.05 Mn 0.035 Zr 0.01 ) 0.90 ]O2.
[0078] The performance of the cathode material C-2 was tested as described above.
[0079] As shown by the results of scanning electron microscopy, the cathode material C-2 had a core-shell structure, with the core having a radius of 1.5 μm and the shell having an outer radius of 5.6 μm. The core and shell had different voids.
[0080] As shown in the results of the pore size, porosity, and pore volume tests, the porosity of the core was 65% and the porosity of the shell was 30%. The change in pore volume under pressure for the positive electrode material C-2 was PV1 / PV0=0.4, PV2 / PV0=1.8, PV3 / PV0=2.7, and PV4 / PV0=3.7 for the pore volume corresponding to a pore size of 90±10 nm.
[0081] The coin cell fabricated using the positive electrode material C-2 of Example 2 had a capacity retention rate of 93.1% after 80 cycles.
[0082] Example 3 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.97:0.02:0.01 to produce a 1.5 mol / L aqueous solution of transition metal salts (1). Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.94:0.02:0.04 to produce a 1.5 mol / L aqueous solution of transition metal salts (2). Nano Nb2O5 was mixed with water to produce a 2 mol / L solution of Nb dopant (3) and a 0.05 mol / L solution of Nb dopant (4). The aqueous solution of transition metal salts (2) was added to the aqueous solution of transition metal salts (1) at a flow rate of 0.2 L / h to produce a mixed aqueous solution of transition metal salts. The Nb dopant solution (4) was added to the Nb dopant solution (3) at a flow rate of 0.1 L / h to generate a mixed Nb dopant solution. At the same time, the mixed aqueous solution of transition metal salts, the mixed Nb dopant solution, 6.0 mol / L NaOH, and 9.0 mol / L NH3·H2O were slowly added to the reactor under stirring. The first coprecipitation was carried out at 53°C under N2 atmosphere at pH 10.0. The first coprecipitation was carried out for 58 hours.
[0083] Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.89:0.055:0.055 to produce a 1.5 mol / L aqueous solution of transition metal salts (5). Nano-ZrO2 was mixed with water to produce a 0.01 mol / L solution of Zr dopant (6) and a 2.0 mol / L solution of Zr dopant (7). The Zr dopant solution (7) was added to the Zr dopant solution (6) at a flow rate of 0.1 L / h to produce a mixed solution of Zr dopant. At the same time, under stirring, the aqueous solution of transition metal salts (5), the mixed solution of Zr dopant, 6.0 mol / L NaOH, and 2.0 mol / L NH3·H2O were slowly added to the reactor where the first coprecipitation had just finished. The second coprecipitation was carried out under N2 atmosphere at pH 11.5 and 56 °C. After 44 hours of the second coprecipitation, the addition of the aqueous solution of transition metal salt (5) was stopped, and after another 0.5 hour reaction, secondary particles with a total particle size of 14.9 μm were obtained.
[0084] The secondary particles were mixed with lithium hydroxide in a ratio of Li:(Ni+Co+Mn)=1.05 and calcined at 740°C for 15 hours in an oxygen atmosphere to obtain the cathode material C-3. 1.05 [(Ni 0.95 Co 0.02 Mn 0.015 Nb 0.015 ) 0.10 ·(Ni 0.905 Co 0.05 Mn 0.035 Zr 0.01 ) 0.90 ]O2. In the core of the positive electrode material C-3, the Nb content decreased from a molar content of 0.02 mol% to 0.01 mol% as it moved radially from the center of the core to the surface of the core. Meanwhile, the Mn content increased from a molar content of 0.01 mol% to 0.02 mol% as it moved radially from the center of the core to the surface of the core. The total amount of Nb and Mn remained at 0.015 mol%. In the shell of the positive electrode material C-3, the Zr content increased from a molar content of 0 to 0.02 mol% as it moved radially from the surface of the core to the surface of the shell. Meanwhile, the Ni content decreased from a molar content of 0.93 mol% to 0.88 mol% as it moved radially from the surface of the core to the surface of the shell. Moreover, the Mn content increased from a molar content of 0.02 mol% to 0.05 mol% as it moved radially from the surface of the core to the surface of the shell.
[0085] The performance of the cathode material C-3 was tested as described above.
[0086] As shown by the results of scanning electron microscopy, the cathode material C-3 had a core-shell structure, with the core having a radius of 3.5 μm and the shell having an outer radius of 4.0 μm. The core and shell had different voids.
[0087] As shown in the results of the pore size, porosity, and pore volume tests, the porosity of the core was 72% and the porosity of the shell was 32%. The change in pore volume under pressure for the positive electrode material C-3 was PV1 / PV0=0.5, PV2 / PV0=2.3, PV3 / PV0=3.1, and PV4 / PV0=5.2 for the pore volume corresponding to a pore size of 90±10 nm.
[0088] The coin cell fabricated using the positive electrode material C-3 of Example 3 had a capacity retention rate of 93.1% after 80 cycles.
[0089] Example 4 Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.87:0.02:0.11 to produce a 1.5 mol / L aqueous solution of transition metal salts (1). Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.84:0.02:0.14 to produce a 1.5 mol / L aqueous solution of transition metal salts (2). Nano Nb2O5 was mixed with water to produce a 2.0 mol / L solution of Nb dopant (3) and a 0.05 mol / L solution of Nb dopant (4). The aqueous solution of transition metal salts (2) was added to the aqueous solution of transition metal salts (1) at a flow rate of 0.2 L / h to produce a mixed aqueous solution of transition metal salts. The Nb dopant solution (4) was added to the Nb dopant solution (3) at a flow rate of 0.1 L / h to generate a mixed Nb dopant solution. At the same time, the mixed aqueous solution of transition metal salts, the mixed Nb dopant solution, 6.0 mol / L NaOH, and 10.0 mol / L NH3·H2O were slowly added to the reactor under stirring. The first coprecipitation was carried out at 52°C with pH 10.8 under N2 atmosphere. The first coprecipitation was carried out for 60 hours.
[0090] Nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 0.60:0.05:0.35 to produce a 1.5 mol / L aqueous solution of transition metal salts (5). Nano-ZrO2 was mixed with water to produce a 0.01 mol / L solution of Zr dopant (6) and a 2.0 mol / L solution of Zr dopant (7). The Zr dopant solution (7) was added to the Zr dopant solution (6) at a flow rate of 0.1 L / h to produce a mixed solution of Zr dopant. At the same time, under stirring, the aqueous solution of transition metal salts (5), the mixed solution of Zr dopant, 6.0 mol / L NaOH, and 4.0 mol / L NH3·H2O were slowly added to the reactor where the first coprecipitation had just finished. The second coprecipitation was carried out under N2 atmosphere at pH 11.5 and 58 °C. After 60 hours of the second coprecipitation, the addition of the aqueous solution of transition metal salt (5) was stopped, and after an additional 1.0 hour of reaction, secondary particles with a total particle size of 16.1 μm were obtained.
[0091] The secondary particles were mixed with lithium hydroxide in a ratio of Li:(Ni+Co+Mn)=1.04 and calcined at 780°C for 15 hours in an oxygen atmosphere to obtain the cathode material C-4. 1.04 [(Ni 0.85 Co 0.02 Mn 0.115 Nb 0.015 ) 0.18 ·(Ni 0.675 Co 0.05 Mn 0.255 Zr 0.02 ) 0.82]O2. In the core of the positive electrode material C-3, the Nb content decreased from a molar content of 0.04 mol% to 0 as it moved radially from the center of the core to the surface of the core. Meanwhile, the Mn content increased from a molar content of 0.06 mol% to 0.1 mol% as it moved radially from the center of the core to the surface of the core. The total amount of Nb and Mn remained at 0.1 mol%. In the shell of the positive electrode material C-4, the Zr content increased from a molar content of 0 to 0.04 mol% as it moved radially from the surface of the core to the surface of the shell. Meanwhile, the Ni content decreased from a molar content of 0.85 mol% to 0.6 mol% as it moved radially from the surface of the core to the surface of the shell. Moreover, the Mn content increased from a molar content of 0.1 mol% to 0.31 mol% as it moved radially from the surface of the core to the surface of the shell.
[0092] The performance of the cathode material C-4 was tested as described above.
[0093] As shown by the results of scanning electron microscopy, the cathode material C-4 had a core-shell structure, with the core having a radius of 4.5 μm and the shell having an outer radius of 3.5 μm. The core and shell had different voids.
[0094] As shown in the results of the pore size, porosity, and pore volume tests, the porosity of the shell was 32% and the porosity of the core was 72%. The change in pore volume under pressure for the positive electrode material C-4 was PV1 / PV0=0.7, PV2 / PV0=2.9, PV3 / PV0=3.8, and PV4 / PV0=5.5 for the pore volume corresponding to a pore size of 90±10 nm.
[0095] The coin cell fabricated using the positive electrode material C-4 of Example 4 had a capacity retention rate of 92.5% after 80 cycles.
[0096] Finally, it should be understood that the above examples are only used to demonstrate the technical solutions of the present invention, but are not used to limit them. Although the present invention has been described in detail with reference to the above examples, those skilled in the art will understand that the technical solutions outlined in the above examples may be modified, and some or all of the described technical features may be substituted with others. Such modifications or substitutions do not cause the corresponding technical solutions to substantially depart from the scope of the technical solutions of the various embodiments of the present invention.
Claims
1. 1. A positive electrode material for a lithium ion battery in the form of secondary particles having a core and a shell, The porosity of the core is greater than that of the shell; a doped nickel-containing cathode material, The porosity of the core is 50-90%; The porosity of the shell is 10 to 50%; the ratio of the core porosity to the shell porosity is greater than 1.2; the average composition of the positive electrode material is Li0.6+δ[(Nix1Coy1M1-x1-y1Dη1)z.(Nix2Coy2M1-x2-y2Gη2)1-z]O2, 0≦δ≦0.6, 0.6≦x1≦1, 0.6≦x2≦1, 0≦y1≦0.4, 0≦y2≦0.4, 0<z<1, 0≦η1≦0.1, 0≦η2≦0.1; Where: M is one or two of Mn and Al; D is one or more of Mo, Ti, Y, W, Ta, Nb, Cr, Sm, Sb, V, La, Ca, Hf, and Zr; G is one or more of Mo, Ta, Zn, Ti, Y, Zr, W, Nb, Cr, Sm, Al, V, La, Ca, Sb, Hf, Mg, and B; the concentration of D gradually decreases radially from the center of the core to the surface of the core; A positive electrode material in which the concentration of G gradually increases radially from the surface of the core to the surface of the shell.
2. the core comprises macropores having a pore size of 50-500 nm, and the porosity of the macropores in the core is 60-80%; 2. The cathode material of claim 1, wherein the shell comprises macropores with a pore size of 50-500 nm, and the porosity of the macropores in the shell is 20-40%.
3. the pore volume of the positive electrode material increases as pressure applied to the positive electrode material increases; The pore volume under pressure of the pores having a pore diameter of 50 to 110 nm in the positive electrode material is PV i It is recorded as where i is 0, 1, 2, 3, and 4, corresponding to the pore volume of the pores when pressures of 0 tons, 1.5 tons, 2.5 tons, 3.5 tons, and 4.5 tons are applied to the cathode material, respectively; The pore volume under pressure is 1<PV 1 / PV 0 < 1.5, 1 < PV 2 / PV 0 <4.0, 1<PV 3 / PV 0 < 6.0, and 1 < PV 4 / PV 0 The positive electrode material of claim 1 , which satisfies the formula:
4. 1. A method for preparing a cathode material for a lithium ion battery in the form of secondary particles having a core and a shell, the cathode material being a doped nickel-containing cathode material, comprising: (1) subjecting a solution of soluble salts containing Ni, Co, and M and a dispersion containing D to a first coprecipitation to form cores of secondary particles; (2) subjecting a solution of soluble salts containing Ni, Co, and M and a dispersion containing G to a second coprecipitation in the presence of the cores of step (1) to form shells on the cores, thereby obtaining secondary particles having a core and a shell, the first co-precipitation is carried out at a pH lower than the pH of the second co-precipitation and at a temperature lower than the temperature of the second co-precipitation; the porosity of the core is greater than the porosity of the shell, the porosity of the core being 50-90%, the porosity of the shell being 10-50%, and the ratio of the porosity of the core to the porosity of the shell being greater than 1.2; (3) a step of converting the secondary particles obtained in step (2) into a positive electrode material, the step including contacting the secondary particles obtained in step (2) with a lithium source material at 300 to 900° C. to obtain the positive electrode material, The lithium source material is Li 2 O, LiOH, LiOH・H 2 O,LiNO 3 , and Li 2 CO 3 and Where: M is one or two of Mn and Al; D is one or more of Mo, Ti, Y, W, Ta, Nb, Cr, Sm, Sb, V, La, Ca, Hf, and Zr; G is one or more of Mo, Ta, Zn, Ti, Y, Zr, W, Nb, Cr, Sm, Al, V, La, Ca, Sb, Hf, Mg, and B.
5. The concentration or flow rate of the dispersion of D is controlled in step (1) such that the concentration of D gradually decreases radially from the center of the core to the surface of the core; 5. The method of claim 4, wherein the concentration or flow rate of the dispersion of G is controlled in step (2) such that the concentration of G gradually increases radially from the surface of the core to the surface of the shell.
6. Step (1) comprises carrying out a first co-precipitation in the presence of a complexing agent; Step (2) comprises carrying out a second co-precipitation in the presence of a complexing agent; The method according to claim 4.
7. The method according to claim 1, wherein the step (1) comprises carrying out a first coprecipitation in the presence of 5 to 12 mol / L of a complexing agent; Step (2) comprises carrying out a second coprecipitation in the presence of 0.1 to 5 mol / L of a complexing agent; The method according to claim 4.
8. The method of claim 6, wherein the complexing agent is one or more selected from the group consisting of ammonia, ammonium sulfate, ammonium chloride, and ammonium nitrate.
Citation Information
Patent Citations
Novel lithium-ion-battery gradient anode material and preparing method thereof
CN108269970A
Lithium ion battery cathode material precursor, lithium ion battery cathode material, preparations methods of lithium ion battery cathode material precursor and lithium ion battery cathode material, and lithium ion battery
CN110422889A
Nickel-containing precursor, nickel-containing composite material, and preparation methods and applications of nickel-containing precursor and nickel-containing composite material
CN112624208A
Lithium iron phosphate positive electrode material as well as preparation method and application thereof
CN113555557A
Positive electrode material and positive plate and battery comprising positive electrode material
CN114447321A
